Marine habitat mapping on Labuan Marine Park, Federal Territory of Labuan, Malaysia - Fazliana Mustajap (2016)
Marine environment consists of many habitats that support marine life. High diversity of marine life forms a complex ecosystem in coastal environments. Therefore, habitat mapping is useful for development and better management planning on marine habitat. Therefore, marine habitat mapping study was conducted in Labuan Marine Park (LMP) area. The objectives of this study were to identify the actual marine habitat (coral reef, macroalgae, sea grass) distribution, to characterize the seabed type, and to create a map of marine habitat and seabed characteristics within the park. LMP is declared as Marine Park since 1994 and only the Marine Park in East Malaysia that managed by Department of Marine Park Malaysia. This park is consists of three islands (Kuraman, Rusukan Besar, Rusukan Kecil) and estimated area of 37.9km2 • The assessments of marine habitat distribution and seabed characteristics were conducted using the side scan sonar (SSS) and supporting images (topography map, satellite, and Google Earth images). The SSS and supporting images were verified by SCUBA diving and sediment assessment on the seabed. The data from previous studies were also used to enhance the results. The classification of seabed was divided into three basic attributes, which are major structure (hard bottom and unconsolidated structures), minor structure (coral, rock, silt, sand), and marine habitat (coral reef, macroalgae, and seagrass) cover. The hard bottom structure is mostly dominant around the islands and at the northern part of the marine park area. Meanwhile, the unconsolidated structure is mostly found in the middle and east part of the park. Coral reef areas are well distributed around the islands in the shallow water area. It is formed from hard and soft corals. The distribution of coral has been recorded at the area between Rusukan Besar Island and Rusukan Kecil Island, and at the southeast part of the park. Meanwhile macro algae mainly found attached to mixed live coral reefs or submerged rocks around islands. Small patches of seagrass habitat located at the middle part of the park. These results are important as detail baseline information on marine habitat for conservation, protection and better management of LMP.